2022
DOI: 10.3389/frobt.2022.745958
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Indicators for Adaptive Human-Swarm Teaming

Abstract: Swarm systems consist of large numbers of agents that collaborate autonomously. With an appropriate level of human control, swarm systems could be applied in a variety of contexts ranging from urban search and rescue situations to cyber defence. However, the successful deployment of the swarm in such applications is conditioned by the effective coupling between human and swarm. While adaptive autonomy promises to provide enhanced performance in human-machine interaction, distinct factors must be considered for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…As swarm autonomy advances, the human's role shifts towards strategic oversight, necessitating robust interfaces for interaction. Recent research has emphasized the importance of bi-directional communication and adaptive systems that integrate the operator's intentions through multi-modal interaction into the swarm's decisionmaking processes [34,54]. Using an immersive interactions environment Adams et al [4] demonstrated the feasibility of the controlling 100 heterogeneous robots while keeping the workload of the operator in an manageable state.…”
Section: Hsimentioning
confidence: 99%
“…As swarm autonomy advances, the human's role shifts towards strategic oversight, necessitating robust interfaces for interaction. Recent research has emphasized the importance of bi-directional communication and adaptive systems that integrate the operator's intentions through multi-modal interaction into the swarm's decisionmaking processes [34,54]. Using an immersive interactions environment Adams et al [4] demonstrated the feasibility of the controlling 100 heterogeneous robots while keeping the workload of the operator in an manageable state.…”
Section: Hsimentioning
confidence: 99%
“…Enhancing the operator's trust involves providing them with accurate and timely feedback about the swarm's state, thereby improving the decision-making process and task performance [11]. The challenge lies in designing interfaces that provide simplified, but informative feedback to operators, enabling them to make informed decisions without being overwhelmed by the swarm's complexities [12]. A possible holistic vision is a "joint human-swarm loop" in which the human becomes a part of the swarm and the robot an extension of the human [13].…”
Section: Related Workmentioning
confidence: 99%
“…Effective human–machine interaction requires that the machine to adapt its behavior according to the user’s cognitive and emotional states, behaviors, performance, and other personal information including identity [ 13 ]. Cognitive biometrics support dynamic recognition of a user’s identity and cognitive and emotional states [ 14 ] and, therefore, are important tools for human–machine interaction in social robots, human–machine systems, and human–swarm teaming systems [ 15 ]; Adaptive control. In closed-loop human–machine adaptive systems, the adaptive control aims to automatically update system parameters by associating the user and system states, so that the user and system can work together effectively and harmoniously.…”
Section: Taxonomy Of Cognitive Biometrics and The Applicationsmentioning
confidence: 99%
“…Effective human–machine interaction requires that the machine to adapt its behavior according to the user’s cognitive and emotional states, behaviors, performance, and other personal information including identity [ 13 ]. Cognitive biometrics support dynamic recognition of a user’s identity and cognitive and emotional states [ 14 ] and, therefore, are important tools for human–machine interaction in social robots, human–machine systems, and human–swarm teaming systems [ 15 ];…”
Section: Taxonomy Of Cognitive Biometrics and The Applicationsmentioning
confidence: 99%